The Solving of Linear Programmable Problems Using Hybrid Algorithms - M. Mohammed, Yasameen; ., .; ., .; ., . (International Journal of Engineering and Technology, 2026)
This paper presents the pointing and investigation of an effectiveness relating a linear mathematical formulation to solve an linear programmable problems based on hybrid algorithms. The hybrid is packages of mathematical programs which contain much occupation required for solve many criteria of linear program (LP) problems. Additionally, a single criterion with linear quadratic problems is solved in this work. For dynamic problems, the hybrid algorithms are useful because the practical algorithm develop the configuration of dynamic problems. The advantage of handling dynamic problems to the user is to produce a simple method of criterion formulation model. The orientation of hybrid is interactive form of process whose a series of problems are answered based changeable situation such as dissimilar objectives functions. The multi objectives criteria could be simply defined and efficient to assist the package. Additionally, the hybrid present more options to diagnostic and verify the problem solving. The suggested approach is hybrid algorithms to solve absolute value equation with no supposition and solvability in linear systems equations followed by linear programs iteratively. The proposed algorithms has been tested and investigated properly.